Art as formelle Bildung in the Modern World in Hegel`s Aesthetics - Domínguez Hernández, Javier (Estudios de Filosofía, 2008)
Formelle Bildung is Hegel`s concept to determine the historical function of art in the modern world. This function contrasts with inhaltliche Bildung or substantielle Bildung that was brought about by art in the Orient and in the Greek Classical World, and in general with the decisive function that art has in the ethos of cultures were art is inseparable from religion, where, according to Hegel, art operates according to a supreme determination. But even though art in modern culture can no longer be Kunstreligión, religion made of art, this doesn`t mean that it has lost its function as a culture factor, but that it still is indispensable in culture, even though it is not for the community to identify itself with the contents that art represents for it, but for individuals to confront themselves in a critico-reflexive way. In the modern world, art is no longer an art of a community but an art of and for a society, in such a way that the State and institucionallity are mediators of it. Art is now autonomous and doesn`t determine doctrinarily nor ideologically the ethos, but the way to provide its intuitions and its representations for reflection, promotes the free exercise of the judgment of individuals. According to Hegel, the “formal” carácter of culture that is provided by modern art, makes art turn into a fundamental matter of cultural policy, where art and public come into the foreground.